The Influence of Organizational Culture, Motivation and Work Environment on Employee Performance PT. Samari Boneraya Palopo - Ampareng, Tenri; Haedar, Haedar; Saharuddin, Saharuddin (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to determine the influence of organizational culture, motivation, and work environment on employee performance at PT. Samari Boneraya Palopo. The method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected by distributing questionnaires to 35 respondents who are permanent employees of the company. The research instrument has been tested for validity and reliability before use. The results of the analysis indicate that partially, organizational culture, motivation, and work environment each have a positive and significant effect on employee performance. The findings also show that simultaneously these three variables contribute significantly to improving performance. Thus, efforts to strengthen a positive work culture, increase motivation, and create a conducive work environment need to be continuously optimized as a strategy to improve human resource performance in the company.